Beyond one-size-fits-all approach: How do various harvesting strategies shape soil microbial diversity in Larix gmelinii (Daxinganling larch) forests of the Greater Khingan Mountains? - Wang, Yufeng; Ta, Na; Zhang, Hao; Li, Min; Liu, Shengwei; Gong, Jiaxing; Song, Yake; Sa, Rula (Frontiers in Microbiology, 2025)
This study analyzed the effects of six harvesting strategies, including primary forests (PF), shelterwood cutting (SC), clear cutting (CC), optional cutting with low intensity (OCL), optional cutting with moderate intensity (OCM), and optional cutting with high intensity (OCH), on soil microbial diversity in Daxinganling larch forests of the Greater Khingan Range. The results showed that the dominant bacterial and fungal phyla were similar across the different harvesting strategies. As the intensity of OC increased, the relative abundances of Proteobacteria and Basidiomycota increased, whereas that of Ascomycota decreased. The highest bacterial alpha diversity was observed in the PF sample plots, whereas the highest fungal alpha diversity was observed in the SC sample plots. OCH significantly reduced bacterial alpha diversity (p < 0.05), and a negative correlation was observed between OC intensity and bacterial alpha diversity. Harvesting strategies had no significant effect on bacterial or fungal beta diversity. In the harvesting strategy sample plots, 14 biological markers were enriched, including the bacterial family SC_l_84 and fungal genus Coniochaeta. Soil nitrogen, phosphorus, and other physical and chemical properties were significantly correlated with different microbial markers. Soil bacterial and fungal communities have diverse genetic and ecological functions. The bacterial and fungal community networks in the PF sample plots were the most complex and stable. OC reduced the complexity and stability of soil bacterial community networks but had the opposite effect on fungal communities. This study preliminarily analyzed the effects of different harvesting strategies on soil microbial diversity in the Greater Khingan Range Larix gmelinii forest, which has practical significance for the functional recovery and protection of the Greater Khingan Range forest ecosystem.